Maths formulas for 0 arithmetic progression
Answers
Answered by
15
Hii There!!!!
In a finite A.P, nth term is given by :-
1=) an = a + ( n - 1 ) × d
here, an = nth term of an A.P
n= number of terms of an A.P
a = first term of A.P
d = common difference between two terms that is a2-a1 .
2=) Sum of "n" terms of an A.P is given by :-
Sn = n/2 [ 2a + ( n-1 ) d]
3) Sn = n/2 [ a + l ]
It is also for Sum of 'n' terms of an A.P having last term (l).
4) Last term from end of an A.P
a(n) = l - (n -1 ) × d
5) For finding common difference, let a1, a2, a3.... be the terms of an A.P
So, common difference = a k+1 - ak
or a2-a1 , a3-a2 , a4-a3 and so on will be the sequence for 'd'.
Hope it helps
In a finite A.P, nth term is given by :-
1=) an = a + ( n - 1 ) × d
here, an = nth term of an A.P
n= number of terms of an A.P
a = first term of A.P
d = common difference between two terms that is a2-a1 .
2=) Sum of "n" terms of an A.P is given by :-
Sn = n/2 [ 2a + ( n-1 ) d]
3) Sn = n/2 [ a + l ]
It is also for Sum of 'n' terms of an A.P having last term (l).
4) Last term from end of an A.P
a(n) = l - (n -1 ) × d
5) For finding common difference, let a1, a2, a3.... be the terms of an A.P
So, common difference = a k+1 - ak
or a2-a1 , a3-a2 , a4-a3 and so on will be the sequence for 'd'.
Hope it helps
Similar questions